2020
DOI: 10.1111/ejh.13509
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of peripheral blood differential counts in hospitalized patients with COVID‐19

Abstract: The pandemic of coronavirus disease 2019 (COVID-19), the disease caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus that emerged in Wuhan, China, in December 2019, has led to significant mortality in hospitalized patients in most affected parts of the world. In the United States, New York emerged as the epicenter of the pandemic, with New Jersey following as the state with the greatest number of cases. 1 According to the Centers for Disease Control and Prevention (CDC), as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
(38 reference statements)
5
20
0
2
Order By: Relevance
“…A single-center retrospective study of 242 COVID-19 cases with 52 patient death, found that the median absolute monocyte count was signi cantly reduced in the death group, while the NLR was signi cantly increased in the survival group [20]. In our research, there was no patient death in the COVID-19 group, with the median monocyte count within the normal range.…”
Section: Discussionsupporting
confidence: 45%
“…A single-center retrospective study of 242 COVID-19 cases with 52 patient death, found that the median absolute monocyte count was signi cantly reduced in the death group, while the NLR was signi cantly increased in the survival group [20]. In our research, there was no patient death in the COVID-19 group, with the median monocyte count within the normal range.…”
Section: Discussionsupporting
confidence: 45%
“…This hyperresponsiveness was also found in other studies [ 224 ]. Some clinical studies report that thrombocytopenia is associated with increased mortality [ 4 , 5 ], whereas other do not [ 215 , 225 ]. This discrepancy might depend on disease severity, comorbidities or the type of care provided.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of thromboembolic complications is elevated in individuals during and after influenza virus infection, for example, a relation which may not be apparent to physicians diagnosing and treating influenza-like illness [ 1 ]. Platelet counts during peak symptomatic disease have also been found to be a marker of disease severity in certain viral infections, [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] or can serve as a first clue towards diagnosing chronic viral infections [ 20 , 21 , 22 , 23 ]. These phenomena are typically not explained by changes in platelet quantity, but rather by the effects of viral infections on platelet function.…”
Section: Introductionmentioning
confidence: 99%
“…In our patients, the WBC were elevated in 33.7% of the patients, while 64% of patients had WBC count within the normal range. The correlation was significant between the infection and WBC count (P = 0.000); the majority of the published studies found a similar correlation with the WBC count (11,12).…”
Section: Discussionmentioning
confidence: 63%